(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Diagnostic microbiology has been transformed by molecular biological technologies for the characterization and identification of microorganisms, which are currently routinely used in specimen processing. The methods of Polymerase Chain Reaction (PCR) have paved the path for this new era through enabling for the quick detection of microorganisms which have been formerly impossible or difficult to detect using standard microbiological methods. Along with detecting fastidious microorganisms, pathogens of public health relevance may currently be detected more quickly using molecular techniques. Molecular approaches have presently evolved beyond identification for detecting antifungal resistance genes as well as providing public health information like genotyping strain characterization. The costs of molecular methods are reducing due to the introduction of multiplex PCR, real-time PCR, and advances in efficiency via automation, and the role of the molecular techniques will continue to grow.